2022
DOI: 10.1142/s2010495222500245
|View full text |Cite
|
Sign up to set email alerts
|

Do the Income and Price Changes Affect Consumption in the Emerging 7 Countries? Empirical Evidence Using Quantile Ardl Model

Abstract: Various empirical studies have been conducted. However, these studies fail to examine the asymmetric effect of income and price across different quantiles of consumption in the emerging 7 countries. This study extends the existing literature using a novel approach called the quantile ARDL model along with the standard nonlinear ARDL model. Findings based on the nonlinear ARDL model indicate that positive shocks in income positively and significantly affect consumption in the short- and long-run. On the other h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Yet, the exchange rate fluctuations of Norway and Canada predominantly drive the volatility in crude oil prices. These findings align with the research conducted by Gohar et al (2022a) provide contrasting conclusions.…”
Section: Gen; Fromsupporting
confidence: 88%
“…Yet, the exchange rate fluctuations of Norway and Canada predominantly drive the volatility in crude oil prices. These findings align with the research conducted by Gohar et al (2022a) provide contrasting conclusions.…”
Section: Gen; Fromsupporting
confidence: 88%
“…They found that CO2 emissions increase due to increased foreign trade openness. [ 42 , 43 , 6 , 44 ]; and [ 29 ] conducted a study in the context of the US, Canada, and other advanced and developing countries. Their findings indicate that foreign trade openness causes a reduction in CO2 emissions.…”
Section: Results Discussionmentioning
confidence: 99%
“…Therefore, the threshold regression is more suitable than the linear regression approach for foreign direct investment and foreign trade openness effect on the CO2 emissions for industrial sectors of India. The authors like [ 49 ] and [ 6 , 45 , 46 ] conducted studies in advanced countries. They concluded the significant effect of foreign direct investment and foreign trade openness on CO2 emissions.,…”
Section: Results Discussionmentioning
confidence: 99%
See 2 more Smart Citations